2021
DOI: 10.1111/brv.12795
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive evolution of viruses infecting marine microalgae (haptophytes), from acute infections to stable coexistence

Abstract: Collectively known as phytoplankton, photosynthetic microbes form the base of the marine food web, and account for up to half of the primary production on Earth. Haptophytes are key components of this phytoplankton community, playing important roles both as primary producers and as mixotrophs that graze on bacteria and protists. Viruses influence the ecology and diversity of phytoplankton in the ocean, with the majority of microalgae–virus interactions described as ‘boom and bust’ dynamics, which are character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 125 publications
0
5
0
Order By: Relevance
“…In these highly proliferative environments, viral infection can lead to the termination of the bloom-forming host population and to the release of large numbers of viral particles ( 29 , 68 ). Although most NCVs seem to have a rather persistent abundance throughout the year ( 30 , 69 , 70 ), such “boom and bust” dynamics following host blooms may provide a temporarily abundant food source for the filter feeders among marine grazers. Furthermore, we posit that owing to their distinct structural characteristics, NCV particles can have a significant contribution to the marine DOM pool.…”
Section: Viruses As a Food Source—are Some Viruses More Nutritious Th...mentioning
confidence: 99%
“…In these highly proliferative environments, viral infection can lead to the termination of the bloom-forming host population and to the release of large numbers of viral particles ( 29 , 68 ). Although most NCVs seem to have a rather persistent abundance throughout the year ( 30 , 69 , 70 ), such “boom and bust” dynamics following host blooms may provide a temporarily abundant food source for the filter feeders among marine grazers. Furthermore, we posit that owing to their distinct structural characteristics, NCV particles can have a significant contribution to the marine DOM pool.…”
Section: Viruses As a Food Source—are Some Viruses More Nutritious Th...mentioning
confidence: 99%
“…Recently, a list of 10 isolated and characterized viruses was published by Sandaa et al (2022) [180]. These viruses can infect marine haptophytes species.…”
Section: Design Of a Viral-based Vector For Microalgae Usementioning
confidence: 99%
“…To date, a total 63 virus that infect eukaryotic microalgae have been isolated and cultured in the laboratory, whereby 50.79% contain dsDNA as genomic material, 15.8% ssDNA, 1.58% dsRNA, and 22.2% ssRNA, whereas 7.93% have not yet been classified [ 163 , 179 ]. Recently, a list of 10 isolated and characterized viruses was published by Sandaa et al (2022) [ 180 ]. These viruses can infect marine haptophytes species.…”
Section: Design Of a Viral-based Vector For Microalgae Usementioning
confidence: 99%
“…Th us, during viral infection, the metabolism of virus-infected cells undergoes enormous changes, which in turn can aff ect coexisting microbial communities and ecological processes. Structural and proteomic studies of the Aureococcus anophageff erens virus revealed that the structure, assembly, and some of the proteins packed inside the AaV particle are similar to those of other giant virus particles, but unlike them, AaV has no fi brils on the outside of its capsid, although fi brils are found on the surface of many viruses from various NCLDV families [52,53].…”
mentioning
confidence: 99%
“…Limited information is available on the role of viruses infecting haptophytes occurring at lower abundances in the sea. It is believed that host populations must exceed a certain threshold density to sustain the virus population, which is true for CeV 01B and other viruses that infect non-fl owering strains, in particular H. ericina [53]. Viruses like CeV employ a variety of strategies to co-exist with their hosts, including a longer latent period and lower virulence, infectivity, and decay compared to viruses that cause acute lytic infection.…”
mentioning
confidence: 99%